The effects of different daily irradiance profiles on Arabidopsis growth, with special attention to the role of PsbS - Schiphorst, Christo; Koeman, Cas; Caracciolo, Ludovico; Staring, Koen; Theeuwen, Tom P. J. M.; Driever, Steven M.; Harbinson, Jeremy; Wientjes, Emilie (Frontiers in Plant Science, 2023)
In nature light is never constant, while in the controlled environments used for vertical farming, in vitro propagation, or plant production for scientific research, the light intensity is often kept constant during the photoperiod. To investigate the effect on plant growth of a varying irradiance during the photoperiod we grew Arabidopsis thaliana under three irradiance profiles: a square-wave profile, parabolic profile with a gradually increasing and then and decreasing irradiance, and a regime comprised of rapid fluctuations in irradiance. The daily integral of irradiance was the same for the three treatments. The leaf area, and plant growth rate and biomass at time of harvest were compared. The plants grown under the parabolic profile had the highest grow rate and biomass. This we could explain by a higher average light-use efficiency for carbon dioxide fixation. Furthermore, we compared the growth of wild type plants with those of the PsbS deficient mutant npq4. PsbS triggers the fast non-photochemical quenching process (qE) that protects PSII from photodamage during sudden increases in irradiance. Based mainly on field and greenhouse experiments the current consensus is that the npq4 mutants grows slower in fluctuating light. However, our data shows that this is not the case for several fluctuating light conditions under otherwise identical controlled climate room conditions.